Birth weight and maternal age among American Indian/Alaska Native mothers: A test of the weathering hypothesis - Jeff A. Dennis (Elsevier, 2019)
Substantial research has examined birth outcomes by race/ethnicity, noting not only disparities by race/ethnicity, but different maternal age patterns in low birth weight (LBW) prevalence. Few studies have examined these disparities among American Indian/Alaska Native (AI/AN) mothers, whose LBW prevalence is below the national average, despite substantial socioeconomic disadvantage among the population. Prior work has hypothesized that AI/AN mothers should exhibit LBW age patterns similar to those seen in NH black mothers as a result of exposure to cumulative stress, trauma, and socioeconomic disadvantage, but this has not been empirically tested. This paper uses data from the 2014-2016 U.S. Birth File, which contains records of all U.S. births for those years to examine maternal age patterns in birth weight among AI/AN mothers. Importantly, this study also considers high birth weight (HBW) births, given higher prevalence of diabetes in the AI/AN population, and proposes that if "weathering" is occurring in this population, HBW prevalence likely will influence the observed maternal age patterns in birth weight, such that prevalence of births in normal range may resemble NH blacks, even if LBW prevalence does not. Findings suggest modest evidence of weathering in AI/AN populations for LBW. Examination of normal birth weight births suggests that inclusion of HBW to the risk profile of AI/AN births better defines birth outcome risk in this population relative to white mothers. Smoking during pregnancy and gestational diabetes were particularly prevalent among AI/AN mothers and present reason for concern in spite of relatively favorable birth outcomes. Keywords: American Indian/Alaska Native, Birth outcomes, Weathering hypothesis